Cognitive neuroscience - Banich, Marie T.
This text balances experimental and clinical perspectives with a survey of a variety of mental functions. In a conversational style, the authors provide clear, accessible explanations of difficult concepts, making use of analogies and case studies to illustrate them. A consistent structure throughout each chapter defines a mental function and the role of each part or parts of the brain in that function, followed by a discussion of what neuropsychological syndromes say about the cognitive and neural organization of the mental function